The Effect of Surfactant and Compatibilizer on Inorganic Loading and Properties of PPO-based EPMM Membranes - Bissadi, Golnaz (Université d'Ottawa / University of Ottawa, 2012)
Hybrid membranes represent a promising alternative to the limitations of organic and inorganic materials for high productivity and selectivity gas separation membranes. In this study, the previously developed concept of emulsion-polymerized mixed matrix (EPMM) membranes was further advanced by investigating the effects of surfactant and compatibilizer on inorganic loading in poly(2,6-dimethyl-1,4-phenylene oxide) (PPO)-based EPMM membranes, in which inorganic part of the membranes originated from tetraethylorthosilicate (TEOS). The polymerization of TEOS, which consists of hydrolysis of TEOS and condensation of the hydrolyzed TEOS, was carried out as (i) one- and (ii) two-step processes. In the one-step process, the hydrolysis and condensation take place in the same environment of a weak acid provided by the aqueous solution of aluminum hydroxonitrate and sodium carbonate. In the two-step process, the hydrolysis takes place in the environment of a strong acid (solution of hydrochloric acid), whereas the condensation takes place in weak base environment obtained by adding excess of the ammonium hydroxide solution to the acidic solution of the hydrolyzed TEOS. For both one- and two-step processes, the emulsion polymerization of TEOS was carried out in two types of emulsions made of (i) pure trichloroethylene (TCE) solvent, and (ii) 10 w/v% solution of PPO in TCE, using different combinations of the compatibilizer (ethanol) and the surfactant (n-octanol). The experiments with pure TCE, which are referred to as a gravimetric powder method (GPM) allowed assessing the effect of different experimental parameters on the conversion of TEOS. The GPM tests also provided a guide for the synthesis of casting emulsions containing PPO, from which the EPMM membranes were prepared using a spin coating technique. The synthesized EPMM membranes were characterized using 29Si nuclear magnetic resonance (29Si NMR), differential scanning calorimetry (DSC), inductively coupled plasma mass spectrometry (ICP-MS), and gas permeation measurements carried out in a constant pressure (CP) system. The 29Si NMR analysis verified polymerization of TEOS in the emulsions made of pure TCE, and the PPO solution in TCE. The conversions of TEOS in the two-step process in the two types of emulsions were very close to each other. In the case of the one-step process, the conversions in the TCE emulsion were significantly greater than those in the emulsion of the PPO solution in TCE. Consequently, the conversions of TEOS in the EPMM membranes made in the two-step process were greater than those in the EPMM membranes made in the one-step process. The latter ranged between 10 - 20%, while the highest conversion in the two-step process was 74% in the presence of pure compatibilizer with no surfactant. Despite greater conversions and hence the greater inorganic loadings, the EPMM membranes prepared in the two-step process had glass transition temperatures (Tg) only slightly greater than the reference PPO membranes. In contrast, despite relatively low inorganic loadings, the EPMM membranes prepared in the one-step process had Tgs markedly greater than PPO, and showed the expected trend of an increase in Tg with the inorganic loading. These results indicate that in the case of the one-step process the polymerized TEOS was well integrated with the PPO chains and the interactions between the two phases lead to high Tgs. On the other hand, this was not the case for the EPMM membranes prepared in the two-step process, suggesting possible phase separation between the polymerized TEOS and the organic phase. The latter was confirmed by detecting no selectivity in the EPMM membranes prepared by the two-step process. In contrast, the EPMM membranes prepared in the one-step process in the presence of the compatibilizer and no surfactant showed 50% greater O2 permeability coefficient and a slightly greater O2/N2 permeability ratio compared to the reference PPO membranes.
Keywords: Gas separation membrane; Hybrid membrane; PPO; Polymerization of TEOS